2020
DOI: 10.1136/annrheumdis-2020-eular.5107
|View full text |Cite
|
Sign up to set email alerts
|

Op0205 phase I Study of D-0120, a Novel Urat1 Inhibitor in Clinical Development for Hyperuricemia and Gout

Abstract: Background:D-0120 is a novel oral selective uric acid transporter (URAT1) inhibitor being developed for the treatment of hyperuricemia and gout by blocking the reabsorption of uric acid (UA) within the renal proximal tubule, thereby reducing serum uric acid concentrations. As a novel URAT1 inhibitor, D-0120 is anticipated to have more potent serum UA reducing effect than the approved URAT1 inhibitor lesinurad, but with less toxicity and wider therapeutic window. The pharmacological potential of D-0120 for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…D-0120 is a novel selective URAT1 inhibitor in phase 2 of development (InventisBio, Shanghai, China). A phase 1 trial showed it was well-tolerated and a phase 2 clinical trial is currently recruiting participants (NCT03923868) ( Zhang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…D-0120 is a novel selective URAT1 inhibitor in phase 2 of development (InventisBio, Shanghai, China). A phase 1 trial showed it was well-tolerated and a phase 2 clinical trial is currently recruiting participants (NCT03923868) ( Zhang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%